ANALYZING MASLOW’S HIERARCHY OF NEEDS, COMPENSATION, AND WORK ENVIRONMENT ON EMPLOYEE RETENTION AT PT BANK MANDIRI (PERSERO) TBK MANADO BRANCH SUDIRMAN - Lahida, Naya W.; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2017)
Abstract: Employee retention is a technique used to retain employees to stay in the company for a certain period. The high retention rate can cause a positive impact for the company. It can be done if the company pays attention to factors such as Maslow’s hierarchy of needs, compensation, and work environment. Organizations that retain their high performers are bound to be successful in performance and at the same time avoid expenses. This study attempt to analyze how Maslow’s hierarchy of needs, compensation, and work environment can effect on employee retention and if those variables are already been applied at the company. This research is using qualitative approach trough interview. The research was conducted at PT Bank Mandiri (Persero) Tbk Manado Branch Sudirman. The population of this research is 10 front-liner of PT Bank Mandiri (Persero) Tbk Manado Branch Sudirman. Based on the results of the analysis it was found that Maslow’s hierarchy of needs, compensation, and work environment have a positive effect against the retention of employees. This suggests that the higher the level of Maslow's hierarchy of needs, compensation, and work environment then the higher employee retention is. Keywords: employee retention, maslow’s hierarchy of needs, compensation, work environment, qualitative study